A Liouville type theorem for non-linear elliptic systems involving advection terms. Issue 12 (2nd December 2018) - Duong, Anh Tuan
Abstract: In this paper, we study the following elliptic system where a is a smooth divergence-free vector field satisfying some decay condition and . We establish a Liouville type result for stable positive solutions of the system in the case and . In particular, when, our result is a natural extension of Cowan [Nonlinear Anal. 2014;104:1–11] to the equation with advection.